The correlation between quality of life and social support in female nurses. Issue 7 (April 2017) - Sun, Ning; Lv, Dong‐Mei; Man, Jing; Wang, Xiao‐yu; Cheng, Qin; Fang, Hong‐li; Fu, Zhen; Liu, Shuang; Wu, Qun‐hong
Abstract : Aims and objectives: To investigate the relationship between quality of life and social support in female nurses. Background: Nurses play an important role in providing care and managing patients' health in hospitals. However, limited studies have shown an association between quality of life and social support in female nurses in China. Design: Questionnaire survey. Methods: To investigate 320 full‐time female nurses in different departments at four comprehensive hospitals in Harbin with a cross‐sectional correlational design using questionnaires. A demographic data questionnaire, menopause‐specific quality of life questionnaire and social support scale were used. Results: The scores on the physical (36·93 ± 17·65) and psychological (17·57 ± 9·45) subscales were higher than those of the vasomotor (4·88 ± 3·48) and sexual (4·53 ± 3·23) subscales of quality of life. The average score of objective support (25·12 ± 4·32) was higher than those of subjective support (9·80 ± 3·04) and utilisation of social support (7·80 ± 1·97). A significant association between quality of life and social support was found ( p < 0·01 ). Conclusions: Social support influenced quality of life. Social support as a buffer for pressure can influence individual stress perception, help individuals cope with pressure and reduce the negative impact of stress on mental and physical health, thus improving different aspects of health. Relevance to clinical practice: Enhancing social support in an active environment would allow female nurses to enjoy a better quality of life in their clinical practice.